Assemblies of Peptide‐Cytotoxin Conjugates for Tumor‐Homing Chemotherapy. (7th January 2019) - Wang, Jinqiang; Hu, Shiqi; Mao, Weiwei; Xiang, Jiajia; Zhou, Zhuxian; Liu, Xiangrui; Tang, Jianbin; Shen, Youqing
Abstract: Peptide‐drug conjugates are prodrugs that have the advantages of precise molecular structure and the direct exploitation of tumor‐homing, penetration or the cellular uptake abilities of the peptides such as the neuropilin‐1 receptor targeting peptide. The prodrugs generally have fast blood clearance due to their low molecular weights and thus are made to self‐assemble into nanostructures, preferably nanosized micelles and vesicles for intravenous administration, to slow their renal clearance. However, most peptidyl prodrugs usually form precipitates, irregular nanofibers or gels that are unsuitable for intravenous injection. Herein, a arginine‐glycine‐aspartic acid‐lysine (RGDK) peptide and cytotoxin 7‐ethyl‐10‐hydroxycamptothecin (SN38) are used to synthesize the tumor‐homing prodrugs (SN38‐Peps) and explore their structure–micelle formation relationships. A small library of SN38‐Peps is obtained using different structures of peptides, linkers, and drug conjugation sites, and the factors affecting the assembly of SN38‐Peps as well as the stability of formed micelles are investigated. An optimized SN38‐Pep, (MOM)SN38(20)‐CRGDK, is finally obtained which forms stable micelles with a hydrodynamic diameter around 110 nm and a fixed drug loading content as high as 35%. The micelles show a prolonged blood circulation, significantly enhanced tumor accumulation, and therefore improved anticancer activity as compared to the non‐targeting prodrug and a clinically used anticancer drug. Abstract : Tumor‐homing prodrugs (SN38‐Peps) composed of RGDK and SN38 are synthesized. After carefully studying the factors affecting the assembly of SN38‐Peps in aqueous solution, an optimized prodrug, (MOM)SN38(20)‐CRGDK with a fixed drug loading content of 35 wt%, forms stable micelles with proper size (110 nm), and shows prolonged blood circulation, significantly enhanced tumor accumulation, and consequently improved anticancer activity.